Draft genome sequence for virulent and avirulent strains of Xanthomonas arboricola isolated from Prunus spp. in Spain. Issue 1 (December 2016) - Garita-Cambronero, Jerson; Palacio-Bielsa, Ana; López, María; Cubero, Jaime
Abstract Xanthomonas arboricola is a species in genusXanthomonas which is mainly comprised of plant pathogens. Among the members of this taxon, X. arboricola pv. pruni, the causal agent of bacterial spot disease of stone fruits and almond, is distributed worldwide although it is considered a quarantine pathogen in the European Union. Herein, we report the draft genome sequence, the classification, the annotation and the sequence analyses of a virulent strain, IVIA 2626.1, and an avirulent strain, CITA 44, ofX. arboricola associated withPrunus spp. The draft genome sequence of IVIA 2626.1 consists of 5, 027, 671 bp, 4, 720 protein coding genes and 50 RNA encoding genes. The draft genome sequence of strain CITA 44 consists of 4, 760, 482 bp, 4, 250 protein coding genes and 56 RNA coding genes. Initial comparative analyses reveals differences in the presence of structural and regulatory components of the type IV pilus, the type III secretion system, the type III effectors as well as variations in the number of the type IV secretion systems. The genome sequence data for these strains will facilitate the development of molecular diagnostics protocols that differentiate virulent and avirulent strains. In addition, comparative genome analysis will provide insights into the plant-pathogen interaction during the bacterial spot disease process.